THE ORIGIN AND SIGNIFICANCE OF THE STORY "GOROUGLI" CREATED BY TURA SULAIMAN - Ibragimov Xayrulla Khamdamovich (Academia Science Repository, 2023)
This article analyzes the uniqueness of the role of samples of oral folk art, especially folk dastans in the works of Tura Suleiman, and the poet’s skillful use of them in his works.